The Hasmoneans and their state: a study in history, ideology, and the institutions - Dąbrowa, Edward (Electrum, 2009)
The history of the Hasmoneans has long caused disputes among scholars, who are far from agreement about the chronology of events, their importance, and the identities of all their actors. There are no indications that such doubts will be resolved anytime soon. The aim of this study, therefore, is not to present a new reconstruction of Hasmonean history, but to describe the institutions of the state they created. This issue usually remains on the fringe of scholarly dispute and has not been closely investigated so far. Nor has an attempt been made at a synthetic presentation of how the Hasmonean state functioned in all its aspects. For this reason, it could not be explored to the full extent possible.